Toxicity in Acid Sulfate Soil, Mekong Delta, Viet Nam: Sources, Dynamics, Effect and Resolve - Ba Le Huy; Hoan Nguyen Xuan; Phong Nguyen Tan; Thanh Le Minh (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
Toxic in water and soil Environment is very difficult for plants and animals even with the people living or surviving with low productivity, mainly due to toxins in the environment. It is produced from the process of oxygen contacting the air with pyrite when the soil is excavated. The research aims to find out the source and kinetics of that toxic source and propose a solution. Toxic substances include Al3+,Fe2+,Fe3+,SO42-, especially with Al3+ in the case of lower pH (2.0\(rightarrow \)4.5). A gents toxic to the environment and organisms sometimes have different effects, but sometimes they are integrated effects. In the environment, the Action of Toxic is very dynamic, it isToxicity dynamic in soil, water: 1-To dry out, the amount of toxins increases, which can cause rice death. The role is to flood rather than liming without washing alum. 2- Acid water with pH=3,8(Al3+<480ppm) can irrigate rice. If it is contaminated with acid water with pH <2.9, the soil will become acidified after 5-6 days. 3- When the rainfall is less than 600 mm, there are a danger toxic effects. But flooded more than (>7 cm) make to increase yield and reduce toxins clearly, 4-Cover land-by plant and green manure cover reduce toxins. 5- Soil moisture has a great influence on toxic fluctuations, especially the organic layer and pyrite layers of the soil are highly acidified. The aluminum salt and it contained Aluminum salt at 30- 40%; the soil becomes acidified quickly and strongly. 6-The alternating oxidation and redox conditions increase the toxicity, especially the pyrite layer and the organic layer. 7-Toxins derived from sediments contain a lot of S+,Fe2+ mangrove plant residue along with microbiological activity in the soil, in the condition of calcium deficiency. From there, shape the Pyrite bar, then Jarosite, followed by sulfuric acid. In conditions of low pH of the environment <2,Al3+ will be created. The aid process eagerly completes the production of ionic poisons: Al3+,Fe2+,Fe3+,SO42-,pH <4,0. And 8-The correlation of toxic ions is a positive correlation, especially SO42- and Fe2+, Al3+, and Fe2+.